Cooperative learning and social skills in three years olds - Ramón Calderón, Rosa (2020)
The general objective of the research was to determine the relationship between cooperative learning and social skills in three-year-old children of an Educational Institution, the type of research was descriptive correlational, the sample was 80 children of initial level, the data collection technique was the observation tab. It is concluded that there is a relationship between Cooperative Learning and Social Skills in the study sample.